2005
DOI: 10.1152/japplphysiol.00437.2004
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive measurement of temperature and fractional dissociation of imidazole in human lower leg muscles using 1H-nuclear magnetic resonance spectroscopy

Abstract: The temperature change of the fractional dissociation of imidazole (alpha-imidazole) in resting human lower leg muscles was measured noninvasively using (1)H-nuclear magnetic resonance spectroscopy at 3.0 and 1.5 T on five normal male volunteers aged 30.6 +/- 10.4 yr (mean +/- SD). Using (1)H-nuclear magnetic resonance spectroscopy, water, carnosine, and creatine in the muscles could be simultaneously analyzed. Carnosine contains imidazole protons. The chemical shifts of water and carnosine imidazole protons r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…However, in gastrocnemius, the C4-H peak was markedly and consistently smaller than the C2-H peak in all subjects (Fig. 1D), which appears to agree with the findings of others, publishing a spectrum from a human gastrocnemius muscle (37,46). Our additional experiments revealed that the testretest reproducibility was good for the C2-H but poor for C4-H peak (M. S. Ö zdemir, H. Reyngoudt, Y.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, in gastrocnemius, the C4-H peak was markedly and consistently smaller than the C2-H peak in all subjects (Fig. 1D), which appears to agree with the findings of others, publishing a spectrum from a human gastrocnemius muscle (37,46). Our additional experiments revealed that the testretest reproducibility was good for the C2-H but poor for C4-H peak (M. S. Ö zdemir, H. Reyngoudt, Y.…”
Section: Resultssupporting
confidence: 91%
“…The present study is possibly the first to apply the technique of proton MRS to noninvasively quantify and monitor the absolute carnosine concentrations in human skeletal muscle with ␤-alanine supplementation. Others have shown that the downfield C2-H and C4-H imidazole resonances of the proton spectrum of human muscle belong to the histidine subunit of carnosine (␤-alanyl-L-histidine) (30,36,46). Pan et al (30) indirectly estimated the absolute carnosine concentration in the forearm muscle of two volunteers from comparison with the estimated creatine concentration and reported values of 5.13 and 8.06 mM.…”
Section: Discussionmentioning
confidence: 99%
“…11,15 In MRS, a Lorentzian line shape is commonly assumed based on a oneexponential transverse relaxation behavior of the spins. The real part of the signal was thus used to estimate spectral parameters in a line shape fitting analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The real part of the signal was thus used to estimate spectral parameters in a line shape fitting analysis. 11 BT for each voxel was calculated from the chemical shift difference between water and N-acetylaspartate signals (⌬H 2 O-NAA) using calibration data from Cady et al: T ( o C)ϭ286.9 to 94*(⌬H 2 O-NAA). 8,15 STIR MR images with ROIs and PET data were transferred to a postprocessing workstation and analyzed using DrView/LINUX image analysis software (Asahi Kasei, Tokyo, Japan).…”
Section: Discussionmentioning
confidence: 99%
“…There are attempts to measure the temperature of deeper layers using ultrasound method [7]. Diffuse optical spectroscopy [8] and magnetic resonance spectroscopy [9] methods are used for temperature control in deeper tissue layers. It has been indicated [10], that by application of IR technology and using special algorithm for data processing (Spatial Temperature Algorithm) it is possible to measure the temperature in the deeper tissue layers.…”
Section: Introductionmentioning
confidence: 99%